2013
DOI: 10.1177/03946320130260s104
|View full text |Cite
|
Sign up to set email alerts
|

Influence on Chondrogenesis of Human Osteoarthritic Chondrocytes in Co-Culture with Donor-Matched Mesenchymal Stem Cells from Infrapatellar Fat Pad and Subcutaneous Adipose Tissue

Abstract: Co-culture of mesenchymal stem cells (MSCs) and articular chondrocytes (ACs) has been proposed for autologous cartilage cell-based therapies, to overcome the issues associated to limited availability of articular chondrocytes (ACs). To evaluate the potentiality of a co-culture approach in aged osteoarthritic patients, MSCs from infrapatellar fat pad (IFP-MSCs) and knee subcutaneous adipose tissue (ASCs) were co-cultured with donor-matched osteoarthritic, expanded and cryopreserved, ACs in a 75%/25% ratio. Co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…A similar reduction was observed in standard spheroids cultured in polypropylene tubes. This observation is coherent with literature data obtained for the chondrogenic 3D culture of mesenchymal stem cells and articular chondrocytes [Giovannini et al, ; Lopa et al, ] and indicates that the increase in spheroid area observed in our experiments over time was due to extracellular matrix deposition and not to cell proliferation.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A similar reduction was observed in standard spheroids cultured in polypropylene tubes. This observation is coherent with literature data obtained for the chondrogenic 3D culture of mesenchymal stem cells and articular chondrocytes [Giovannini et al, ; Lopa et al, ] and indicates that the increase in spheroid area observed in our experiments over time was due to extracellular matrix deposition and not to cell proliferation.…”
Section: Discussionsupporting
confidence: 94%
“…As hypothesized for the PDMS chips, the multi‐well construct produced in this study can be used for the co‐culture of different cell types, which is usually performed by more standard 3D models, such as spheroids [Giovannini et al, ; Lopa et al, ; Wu et al, ] and random cell dispersion in 3D scaffolds [Hildner et al, ; Sabatino et al, ]. The controlled distribution of mesenchymal stem cells and bovine chondrocytes in an implantable multi‐well scaffold has been performed in a recent study screening the effect of several extracellular matrix components on the chondrogenesis of MSCs co‐cultured with bovine chondrocytes [Higuera et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopa et al . previously demonstrated no positive effect of co-culture with adipose derived MSCs 25 . That study used cryogenically preserved cells and had expanded the cells with the use of transforming growth factor- β1 (TGF-β1), which may have resulted in their negative finding.…”
Section: Discussionmentioning
confidence: 84%
“…Total mRNA (up to 2.5 μg) was reverse-transcribed into cDNA using SuperScript® VILO™ Master Mix. cDNA was ampli ied with the TaqMan® Gene Expression Master Mix (Applied Biosystems by Life Technologies, Grand Island, NY, USA) on an ABI 7900HT Sequence Detection System (Applied Biosystems) and probes speci ic for GAPDH, a housekeeping gene that has served as a baseline in several studies on chondrocyteprogenitor interaction and MSC-chondrocyte co-culture [32][33][34][35][36][37], sex-determining region Y (SRY)-box 9 (SOX9), ACAN, Lubricin, Col XI, Col X, VEGF-A, Col I, alkaline phosphatase (ALP), and osterix were used. Known primer sequences for these species appear in Table 1, and where primer sequences are proprietary, the company name and catalogue number are given.…”
Section: Rna Isolation and Analysismentioning
confidence: 99%